Role of plants in nitrogen and sulfur transformations in floating hydroponic root mats: A comparison of two helophytes. (1st October 2016) - Saad, Rania A.B.; Kuschk, Peter; Wiessner, Arndt; Kappelmeyer, Uwe; Müller, Jochen A.; Köser, Heinz
Abstract: Knowledge about the roles helophytes play in constructed wetlands (CWs) is limited, especially regarding their provision of organic rhizodeposits. Here, transformations of inorganic nitrogen and sulfur were monitored in a CW variety, floating hydroponic root mat (FHRM), treating synthetic wastewater containing low concentration of organic carbon. Two helophytes, Phragmites australis and Juncus effusus, were compared in duplicates. Striking differences were found between the FHRM of the two helophytes. Whereas ammonium was removed in all FHRMs to below detection level, total nitrogen of 1.15 ± 0.4 g m −2 d −1 was removed completely only in P. australis systems. The mats with J. effusus displayed effective nitrification but incomplete denitrification as 77% of the removed ammonium-nitrogen accumulated as nitrate. Furthermore, the P. australis treatment units showed on average 3 times higher sulfate-S removal rates (1.1 ± 0.45 g m −2 d −1 ) than the systems planted with J. effusus (0.37 ± 0.29 g m −2 d −1 ). Since the influent organic carbon was below the stoichiometric requirement for the observed N and S transformation processes, helophytes' organic rhizodeposits apparently contributed to these transformations, while P. australis provided about 6 times higher bioavailable organic rhizodeposits than J. effusus . Highlights: Helophyte species play different roles in constructed wetlands (CWs). Species may decisively influence the pollutants' transformation scenarios in CWs. TN removal was >4 times higher in Phragmites australis than Juncus effusus CWs. Sulfur was removed 3 times more in P. australis CWs. Rhizodeposits constituted an important source of electron donors for N and S transformation processes.